2017
DOI: 10.1002/chem.201604878
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Fibrous Network of Na0.21MnO2 for Aqueous Sodium‐Ion Hybrid Supercapacitors

Abstract: Sodium-ion hybrid supercapacitors are potential energy-storage devices and have recently received enormous interest. However, the development of cathode materials and the use of nonaqueous electrolyte remain a great challenge. Hence, aqueous Na-ion hybrid supercapacitors based on a three-dimensional network of NaMnO were developed. The cathode material was synthesized by the electro-oxidation of potassium manganese hexacyanoferrate nanocubes. The oxidized compound was confirmed to be Na MnO by various physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 58 publications
1
30
1
Order By: Relevance
“…In summary, Na-ion based transition metal compounds with 3D porous framework, large-sized tunnels, improved conductivity and cost-effective characteristics can be used as electrodes in sodium ion storage systems. As mentioned above, the chosen Na 0.44 MnO 2 and Na 0.21 MnO 2 with excellent cycling stability and good rate performance have been reported as cathodes in the Ti 3 C 2 T x /CNT// Na 0.44 MnO 2 and rGO//Na 0.21 MnO 2 SICs, respectively [41,80]. Moreover, the alluaudite-type Na 2 Fe 2 (SO 4 ) 3 with a theoretical capacity of 120 mA h g −1 and a high redox voltage of 3.8 V has been used as cathode to fabricate hybrid sodium ion pseudocapacitor by Zhu et al [77].…”
Section: Mxenesmentioning
confidence: 86%
“…In summary, Na-ion based transition metal compounds with 3D porous framework, large-sized tunnels, improved conductivity and cost-effective characteristics can be used as electrodes in sodium ion storage systems. As mentioned above, the chosen Na 0.44 MnO 2 and Na 0.21 MnO 2 with excellent cycling stability and good rate performance have been reported as cathodes in the Ti 3 C 2 T x /CNT// Na 0.44 MnO 2 and rGO//Na 0.21 MnO 2 SICs, respectively [41,80]. Moreover, the alluaudite-type Na 2 Fe 2 (SO 4 ) 3 with a theoretical capacity of 120 mA h g −1 and a high redox voltage of 3.8 V has been used as cathode to fabricate hybrid sodium ion pseudocapacitor by Zhu et al [77].…”
Section: Mxenesmentioning
confidence: 86%
“…In addition to those, the significant influence of the intercalated alkali-ions (e.g. Li + , Na + and K + ) themselves on the pseudocapacitive contribution should be taken into account when analyzing the specific capacitance increase [121].…”
Section: Supercapacitorsmentioning
confidence: 99%
“…As a transition metal element, manganese is appealing in energy storage field for its diversity of stable oxidation states (Mn 2+ , Mn 3+ , Mn 4+ ), crystal structures, morphology, and porosity . For example, MnO 2 have been widely used as electrode materials in supercapacitors . Na x MnO 2 is a kind of attractive battery‐type cathode material for NIBs, i.e., Na 0.44 MnO 2 , as shown in Figure a, because of its large‐size tunnels into which Na + can be readily inserted .…”
Section: Materials For Sodium‐ion Capacitorsmentioning
confidence: 99%
“…Subsequently, Wasiński et al demonstrated a novel NIC based on Na 0.4 MnO 2 cathode and AC anode, giving rise to a specific capacitance of 17.4 F g −1 . An aqueous NIC was developed by Chen and co‐workers in 2017, which take Na 0.21 MnO 2 and rGO as cathode and anode, respectively . The device exhibits a large operational voltage window of 0–2.7 V without any side effect (water splitting) for 1000 cycles with a capacitance retention of 86.7%.…”
Section: Materials For Sodium‐ion Capacitorsmentioning
confidence: 99%